Electronic Longitudinal Alcohol Study in Communities (ELAStiC) Wales – protocol for platform development - Laszlo Trefan; Ashley Akbari; Shantini Paranjothy; Daniel Mark Farewell; Andrea Gartner; David Fone; Giles Jeremy Greene; Anette Evans; Ann Smith; Victor Adekanmbi; Jonathan Kennedy; Ronan Anthony Lyons; et al. (International Journal of Population Data Science, 2019)
Introduction